Textual Evidence (CCSS RI. 7.1). - Educational, Lorenz (Common Core State Standards., 2014)
Aligns to CCSS RI. 7.1: Cite several pieces of textual evidence to support analysis of what the text says explicitly as well as inferences drawn from the text.